2017
DOI: 10.1002/app.45110
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of polyamide TFC membranes via redox‐initiated graft polymerization of acrylic acid

Abstract: In this work, the redox‐initiated graft polymerization of acrylic acid (AA) onto the surface of polyamide thin film composite membranes has been carried out to enhance membrane separation and antifouling properties. The membrane surface characteristics were determined through the attenuated total reflection Fourier transform infrared spectra, scanning electron microscopy, atomic force microscopy, and water contact angles. The membrane separation performance was evaluated through membrane flux and rejection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Additionally, Sakar et al [ 47 ] used dendrimer-based coatings to reduce fouling effects. Recently, Ngo et al [ 48 ] used redox initiated graft polymerization to coat TFC membrane with hydrophilic poly(acrylic acid). The coated membrane had lower roughness than the virgin one, and subsequently better fouling resistance and water flux was achieved.…”
Section: Modification Of Membrane Surfacementioning
confidence: 99%
“…Additionally, Sakar et al [ 47 ] used dendrimer-based coatings to reduce fouling effects. Recently, Ngo et al [ 48 ] used redox initiated graft polymerization to coat TFC membrane with hydrophilic poly(acrylic acid). The coated membrane had lower roughness than the virgin one, and subsequently better fouling resistance and water flux was achieved.…”
Section: Modification Of Membrane Surfacementioning
confidence: 99%
“…However, the broad complex band around 3300 cm −1 intensified due to the increase in the density of functional groups such as -OH, and C-H groups from GO and polymer (Figure 9b) [36]. Moreover, a new peak appeared at 1720 cm −1 confirming the incorporation of the carboxylic acid group (carbonyl, C=O) into the membrane from GO and PAA (Figure 9c) [37]. Figure 10 shows the Raman spectra of the RO and PAA-GO@RO optimized membrane.…”
Section: Membrane Surface Morphology and Functional Group Analysismentioning
confidence: 97%
“…Moreover, membrane surface properties also influence membrane fouling [42]. Most of the existing research has shown that the hydrophobic membrane is more prone to membrane fouling, and therefore, hydrophilization of the membrane is recommended to inhibit fouling [37,43]. Similarly, membrane smoothness also helps to prevent membrane fouling by not providing sites for foulant attachment [44].…”
Section: Inorganic Fouling Testmentioning
confidence: 99%
“…There are several methods for modifying the surface of NF membranes to achieve membrane fouling removal [ 29 ]. The methods available are UV photografting [ 30 ], plasma-assisted grafting [ 31 ], redox-initiated grafted polymerisation of acrylic acid [ 32 ] and embedding nanoparticles coupled with graphene oxide [ 33 ].…”
Section: Nanofiltration Membranementioning
confidence: 99%